From Innovation to Impact: Trends and Effectiveness of Interactive E-Books in Elementary Indonesian Language Learning (2020-2025) - Rahmah Rivandani Ihsanah; Yeri Sutopo; Sri Sukasih; Bambang Subali; Nuni Widiarti (Journal of Educational Sciences, 2026)
This study aims to identify and analyze the trends in the development and effectiveness of interactive e-books in Indonesian language learning at the elementary school level based on scientific literature. This research employed a Systematic Literature Review (SLR) method using the PRISMA 2020 framework, involving 20 scientific articles published between 2020 and 2025. The data were obtained from several databases, including Google Scholar, Garuda, SINTA, DOAJ, and reputable international journals. The data collection instrument consisted of an extraction sheet containing information on title, authors, publication year, research methods, research subjects, types of e-books, and research findings. The data were analyzed descriptively and thematically to identify research patterns, characteristics of e-book features, and their impact on learning. The results indicate that interactive e-books are generally developed using the Research and Development (R&D) approach, integrating multimedia features such as audio, animation, video, and interactive quizzes. These features significantly enhance student engagement in the learning process. The use of interactive e-books has been proven effective in improving reading comprehension, learning motivation, learning outcomes, and digital literacy among elementary school students. These findings suggest that interactive e-books have substantial potential as innovative learning media.